The Quality Control of Tea by Near-Infrared Reflectance (NIR) Spectroscopy and Chemometrics - Ming-Zhi Zhu; Beibei Wen; Hao Wu; Juan Li; Haiyan Lin; Qin Li; Yinhua Li; Jianan Huang; Zhonghua Liu (Journal of Spectroscopy)
Tea is known to be one of the most popular beverages enjoyed by two-thirds of the world’s population. Concern of variability in tea quality is increasing among consumers. It is of great significance to control quality for commercialized tea products. As a rapid, noninvasive, and nondestructive instrumental technique with simplicity in sample preparation, near-infrared reflectance (NIR) spectroscopy has been proved to be one of the most advanced and efficient tools for the control quality of tea products in recent years. In this article, we review the most recent advances and applications of NIR spectroscopy and chemometrics for the quality control of tea, including the measurement of chemical compositions, the evaluation of sensory attributes, the identification of categories and varieties, and the discrimination of geographical origins. Besides, challenges and future trends of tea quality control by NIR spectroscopy are also presented.